COVID-19 Vaccine Booster Dose Willingness among Patients with Inflammatory Bowel Disease on Infliximab and Vedolizumab: A Cross-Sectional Study - Mohammad Shehab; Fatema Alrashed; Ahmad Alfadhli (Vaccines, 2022)
Background: Vaccination has been effective in preventing COVID-19 infections and related mortality. However, waning immunity after two-dose vaccination prompted health authorities to recommend a third dose of COVID-19 vaccine to boost immunity. The aim of our study was to assess willingness to receive a third (booster) dose among patients with inflammatory bowel disease (IBD). Methods: A cross-sectional study was performed at an IBD tertiary care center. Patients were recruited at the infusion room from 1 January 2022 to 31 March 2022. The primary outcome was the prevalence of a third (booster) dose of the BNT162b2 vaccine in infliximab- or vedolizumab-treated patients with IBD. The secondary outcome evaluated whether the prevalence of a third (booster) dose of the BNT162b2 vaccine differed based on type of COVID-19 vaccine, gender, age, type of biologic therapy, and citizenship. Results: In total, 499 patients with IBD were included in this study. The median age was 34.5 years, and 60% had ulcerative colitis (UC). Among the study participants, 302 (60.5%) patients were vaccinated with BNT162b2, and 197 (39.5%) were vaccinated with ChAdOx1 nCoV-19. Of the total number of participants, 400 (80.2%) were receiving infliximab, and 99 (19.8%) were receiving vedolizumab. Overall, 290 (58.1%) of the included patients were willing to receive the third (booster) dose. Patients vaccinated with BNT162b2 were more likely to be willing to receive a booster dose compared to patients vaccinated with ChAdOx1 nCoV-19 (201 (66.5%) vs. 103 (52.0%), p = 0.014). Infliximab-treated patients were more likely to be willing to receive a booster dose compared to patients receiving vedolizumab (310 (77.5%) vs. 62 (62.6%), p = 0.002). There was no statistical difference in willingness to receive a booster dose in terms of age, nationality, or gender. Conclusions: The percentage of patients with IBD willing to receive or having already received a third (booster) dose of BNT162b2 vaccine was lower compared to the general population. In addition, patients who received two doses of BNT162b2 vaccines were more likely to be willing to receive a third (booster) dose compared to patients who received ChAdOx1 nCoV-19. Patients treated with infliximab were more likely to be willing to receive a third (booster) dose of COVID-19 vaccine.